An analysis of the financial implications of different tillage systems within different crop rotations in the Swartland area of the Western Cape, South Africa - Knott, Stuart Charles (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2015.